Synthesis and characterization of polyurethane-based self-luminous pavement coatings: a performance evaluation study - Qinghe Lu; Xiajun Liu; Zhen Lu; Ke Li; Ke Li (Frontiers in Materials, 2024)
Improving the nighttime vision of drivers is essential, given the growing advancements in urban transportation. In this study, polyurethane-based self-luminous pavement coatings (PSCs) were prepared by doping luminous powders (LPs) into the polyurethane materials. The superior optical properties and chemical stabilities of these coatings were ensured by synthesizing the polyurethane-based material. Then, the PSCs were evaluated for their comprehensive performances, such as luminescence, aging resistance, and abrasion resistance, using various characterization methods, including fluorescence spectral analysis, Fourier-transform infrared spectroscopy, fluorescence microscopy, and mechanical property testing. The results show that the 50-mesh LP has the optimal overall performance, with an initial luminescence that exceeds those of the 100 and 400 meshes. The initial brightness of the PSC is mainly influenced by the LP and increases with dosage. The lattice structure and luminescent properties of the luminescent material did not change after coating preparation. The peak excitation wavelength of 420 nm implies that the coating has the best excitation effect under UV light. The primer-marking coating effectively improves the abrasion resistance of the PSC, and the mass loss of the PSC with a coating thickness of 0.4 kg/m2 is 52.9% of that without the primer-marking coating, with the optimal coating thickness being 0.6 kg/m2. This research provides an innovative solution to improve nighttime roadway lighting, which provides useful support for the sustainable development of urban transportation infrastructures and construction of intelligent transportation systems.